1997
DOI: 10.1073/pnas.94.10.5361
|View full text |Cite
|
Sign up to set email alerts
|

Functional antioxidant responsive elements

Abstract: Exposure of human and rodent cells to a wide variety of chemoprotective compounds confers resistance against a broad set of carcinogens. For a subset of the chemoprotective compounds, protection is generated by an increase in the abundance of protective enzymes like glutathione S-transferases (GST). Antioxidant responsive elements (AREs) mediate the transcriptional induction of a battery of genes which comprise much of this chemoprotective response system. Past studies identified a necessary ARE ''core'' seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
456
1
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 657 publications
(476 citation statements)
references
References 41 publications
15
456
1
4
Order By: Relevance
“…Studies on the role of the GC box in constitutive gene expression, however, are controversial. Similarly to what was observed here with rat GGT promoter 5, deletion of the GC box abrogated EpRE-mediated basal expression of the rat GSH S-transferase Ya [55] and cystine/glutamate exchange transporter [56]; however, deletion of the GC box had no effect on the constitutive expression of hGCLm and mice heme oxygenase-1 (HO-1) [54,57].…”
Section: Discussionsupporting
confidence: 74%
“…Studies on the role of the GC box in constitutive gene expression, however, are controversial. Similarly to what was observed here with rat GGT promoter 5, deletion of the GC box abrogated EpRE-mediated basal expression of the rat GSH S-transferase Ya [55] and cystine/glutamate exchange transporter [56]; however, deletion of the GC box had no effect on the constitutive expression of hGCLm and mice heme oxygenase-1 (HO-1) [54,57].…”
Section: Discussionsupporting
confidence: 74%
“…In line with this, the role of Nrf2 in mediating the co-regulation of the phase II enzymes and ABC transporters was further confirmed by the discovery of AREs (antioxidant response elements) in many of these genes. For example, the AREs have been detected in many genes of the phase II enzymes including the GST (Wasserman and Fahl, 1997;Kwak et al, 2003), GCLC (Kwak et al, 2003), and UGT1A1 genes (Yueh and Tukey, 2007); ARE-like sequences were also identified in the mouse ABCCs (Vollrath et al, 2006). These finding suggest that a common regulatory mechanism is possible for the GST, GCLC and ABCC genes (Meijerman et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…It is known from the literature, that estrogens can regulate the expression of phase II enzymes via cis-active DNA elements, so-called antioxidant/electrophile response element ARE, which are located in promoter regions of corresponding genes [44]. For instance, it was described, that 17b-estradiol [E2] administration induced the decrease of catalytic activity of GSTs in cervical cells using ARE-mediated mechanism.…”
Section: Gstm1 Gstt1mentioning
confidence: 99%